Impact of high MELD scores on CMV viremia following liver transplantation. Issue 1 (10th January 2023) - Freedman, Sari R.; Saunders, Kenneth; Plazak, Michael E.; Ravichandran, Bharath R.; Saharia, Kapil K.; Masters, Brian M.; Sparkes, Tracy
Abstract: Introduction: Advanced liver disease or cirrhosis is associated with an increased risk of infections; however, the impact of high pretransplant model for end‐stage liver disease (MELD) score on cytomegalovirus (CMV) viremia after liver transplantation is unknown. Methods: This single‐center, retrospective, cohort study evaluated CMV high‐risk (CMV immunoglobulin G D+/R−) liver transplant recipients who received valganciclovir prophylaxis for 3 months between 2009 and 2019. Patients were stratified by pretransplant MELD score of <35 (low MELD) and ≥35 (high MELD). The primary outcome was 12‐month CMV viremia, and secondary outcomes included CMV resistance and tissue invasive disease, mortality, biopsy‐proven acute rejection (BPAR), leukopenia, and thrombocytopenia. Multivariable Cox proportional‐hazards modeling was used to assess the association of MELD score with the time to CMV viremia. Results: There were 162 and 79 patients in the low and high MELD groups, respectively. Pretransplant MELD score ≥35 was associated with an increased risk of CMV viremia (hazard ratio [HR] 1.73; confidence interval 1.06–2.82, p = .03). CMV viremia occurred at 162 ± 61 days in the low MELD group and 139 ± 62 days in the high MELD group. Although BPAR occurred early at 30 days (13–59) in the low‐MELD group and at 18 days (11–66) in the high‐MELD group ( p = .56), BPAR was not associated with an increased risk of CMV viremia (HR 1.55 [0.93–2.60], p = .1). Discussion: MELD scores ≥35 were associated with an increased hazards of CMV viremia. In liver transplant recipients with MELD scores ≥35 who are CMV high‐risk, additional CMV intervention may be warranted. Abstract :